Efficacy and Safety of Electrical Ventricular Defibrillation: The Experiment and Clinic - V. A. Vostrikov (Общая реаниматология, 2012)
The paper provides the results of the 1990—2010 experimental and clinical studies on the optimization of the efficiency of electrical ventricular defibrillation using the Russian bipolar quasi-sinusoidal impulse. The comprehensive study of the influence of major cardiac and extracardiac factors, such as heart failure, the type and duration of fibrillation, its amplitude and frequency characteristics, chest resistance, electrode sizes, administration of antiarrhythmic drugs, and phase 2 impulse amplitude on the efficiency and safety of defibrillation, could formulate a number of new propositions and solve some methodological and methodic issues. The dose-dependent effectiveness of the quasi-sinusoidal impulse has been first investigated in patients with induced, spontaneous primary and secondary fibrillation and ventricular tachycardia. Low-energy (Key words: defibrillation, bipolar quasi-sinusoidal impulse.